2014
DOI: 10.1016/j.jtcvs.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after definitive repair for tetralogy of Fallot with preservation of the pulmonary valve annulus

Abstract: The long-term outcomes after definitive repair of tetralogy of Fallot with preservation of the PV annulus were excellent. Although isolated, monofocal premature ventricular contractions were frequently observed, fatal ventricular arrhythmia was not. The indication should not only be decided by the PV annulus size, but also by the valvular morphology to maintain long-term PV competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 23 publications
2
36
2
Order By: Relevance
“…Pulmonary valve z-score 4 or less was found to be a predictor of recurrent RVOT obstruction in other series [ 13 ] and our current strategy is to preserve the pulmonary valve in patients without severe annular hypoplasia. Hoashi et al, [ 14 ] found that pulmonary valve z-score was not a predictor of recurrent ROVT obstruction but z-score less than − 2 was a predictor of progressive pulmonary regurgitation which was not found in our study, the degree of pulmonary regurgitation regressed by one grade in 10 patients during the follow up. The most common pulmonary valve morphology encountered was a bicuspid valve followed by tricuspid morphology.…”
Section: Discussioncontrasting
confidence: 85%
“…Pulmonary valve z-score 4 or less was found to be a predictor of recurrent RVOT obstruction in other series [ 13 ] and our current strategy is to preserve the pulmonary valve in patients without severe annular hypoplasia. Hoashi et al, [ 14 ] found that pulmonary valve z-score was not a predictor of recurrent ROVT obstruction but z-score less than − 2 was a predictor of progressive pulmonary regurgitation which was not found in our study, the degree of pulmonary regurgitation regressed by one grade in 10 patients during the follow up. The most common pulmonary valve morphology encountered was a bicuspid valve followed by tricuspid morphology.…”
Section: Discussioncontrasting
confidence: 85%
“…They reported that aggressive right ventricle outflow tract muscle resection contributed to the prevention of recurrent right ventricle outflow tract obstruction, even though patients had a pressure ratio (right ventricle/aorta) >0.7 and a small pulmonary valve annulus. 9 Similarly, we admitted the concern about subvalvar stenosis on echocardiogram in operating room, but we could not suggest any cut-off pressure ratio in operating room from our study. There are limitations in evaluating pressure gradient or right ventricular pressure in operating room.…”
Section: Discussionmentioning
confidence: 57%
“…8 Twenty-year data are emerging for a valve-sparing approach, with encouraging freedom from ventricular arrhythmia, but era differences make comparison difficult. 9 The Rotterdam data strengthen evidence that TAP is a factor predicting late dysfunction, arrhythmia, or death, which finds support in some but not all series.…”
Section: At the Front Endmentioning
confidence: 80%